Mediated Non-geminate Recombination in Ternary Organic Solar Cells Through a Liquid Crystal Guest Donor - Yin, Ao; Zhang, Dongyang; Wang, Jianqiu; Zhou, Huiqiong; Fu, Zhiqiang; Zhang, Yuan (Frontiers in Chemistry, 2020)
The approach via ternary blends prompts the enlargement of absorbed photons and resultant photocurrent in organic solar cells (OSCs). In contrast to actively reported high efficiency ternary OSCs, little is known about charge recombination properties and carrier loss mechanisms in these emerging devices. Here via the introduction of a small molecule BTR guest donor into the PCE-10:PC71BM binary system, we show that the photocarrier losses via recombination paths are mitigated with respect the binary OSC, primarily owing to the small bi-molecular recombination rate in BRT:PC71BM with balanced mobility. The gain of the fill factor in ternary devices are reconciled by the shift on the equilibrium between charge exaction and recombination in the presence of BTR toward the former process. With these modifications, the power conversion efficiency in ternary solar cells receive a boost from 8.8% (PCE-10:PC71BM) to 10.88%. Moreover, we found that the voltage losses in the ternary cell can become mitigated as well, which is associated with the rise of charge transfer states regarding that in the PCE-10:PC71BM blends. These benefits induced by the third guest donor frame a useful guiadance to attain effective meliorations on key photophysical processes governing ultimate device efficiencies in organic ternary solar cells.